The comparison of Dietary Inflammatory Index (DII) value in obesity and non-obesity - Fani Khairunnisa Rakhman; Lirista Dyah Ayu Oktafiani (Department of Nutrition at the Health Polytechnic of Aceh, Ministry of Health, 2024)
Obesity is a chronic low-grade inflammatory condition that occurs in the White Adipose Tissue (WAT). Diet is the strongest factor regulating energy balance and influencing inflammatory responses in the body. This inflammatory response can be calculated using the Dietary Inflammatory Index (DII). The aim of this research was to determine the differences between DII values for obese and non-obese people in the work area of the Sumbersari Public Health Center, Jember Regency, which was carried out from May to June 2023. This was a cross-sectional study with sample selection through a simple random sampling method. Thirty participants were included in each group. Data collection was carried out using the Semi-Quantitative Food Frequency Questionnaire (SQ-FFQ), and the data were analyzed using an independent t-test. The normality test was performed using the Kolmogorov-Smirnov test, and the data were normally distributed. The results obtained that There was a significant difference (p=0,000) between the DII values of the normal and obese groups. It is known that the average DII value in the normal group was +2,29 and in the obese group was +1,32, indicating that the normal group had a higher pro-inflammatory diet than the obesity group. In conclusion, there was a significant difference between the DII values in obese and non-obese groups in the working area of the Sumbersari Community Health Center, Jember Regency.